Engineering the hydroxyl content on aluminum oxyhydroxide nanorod for elucidating the antigen adsorption behavior - Ge Yu; Zhihui Liang; Zilan Yu; Min Li; Wenqi Yang; Yawei Zhang; Yuhang Zhao; Cheng Yang; Changying Xue; Li Shi; Bingbing Sun (npj Vaccines, 2022)
Abstract The interaction between the aluminum salt-based adjuvants and the antigen in the vaccine formulation is one of the determining factors affecting the immuno-potentiation effect of vaccines. However, it is not clear how the intrinsic properties of the adjuvants could affect this interaction, which limits to benefit the improvement of existing adjuvants and further formulation of new vaccines. Here, we engineered aluminum oxyhydroxide (AlOOH) nanorods and used a variety of antigens including hepatitis B surface antigen (HBsAg), SARS-CoV-2 spike protein receptor-binding domain (RBD), bovine serum albumin (BSA) and ovalbumin (OVA) to identify the key physicochemical properties of adjuvant that determine the antigen adsorption at the nano-bio interface between selected antigen and AlOOH nanorod adjuvant. By using various physicochemical and biophysical characterization methods, it was demonstrated that the surface hydroxyl contents of AlOOH nanorods affected the adsorptive strength of the antigen and their specific surface area determined the adsorptive capacity of the antigen. In addition, surface hydroxyl contents had an impact on the stability of the adsorbed antigen. By engineering the key intrinsic characteristics of aluminum-based adjuvants, the antigen adsorption behavior with the aluminum adjuvant could be regulated. This will facilitate the design of vaccine formulations to optimize the adsorption and stability of the antigen in vaccine.